Answer:
-35
Step-by-step explanation:
PEMDAS
Answer:
10.8 cm
Step-by-step explanation:
Using cosine law
g² = 7.1² + 6.7² - 2(7.1)(6.7)cos(103)
g² = 116.7018433
g = 10.80286274
Hi there!
To solve this problem using substitution, we need to set x equal to a value and substitute it into the other equation.
Since
x - 4y = 5,
x = 5 + 4y
3x - 7y = 10
3(5 + 4y) - 7y = 10
15 + 12y - 7y = 10
15 + 5y = 10
5y = -5
y = -1
Now that we know y is -1, we can substitute it back into the equation to find x:
y = -1
x - 4y = 5
x - 4(-1) = 5
x - (-4) = 5
x + 4 = 5
x = 1
So, your answers are x = 1 and y = -1.
Hope this helps!
5*7/8 = 4 3/8
5/1 * 7/8 = 35/8
convert into mixed number because numerator is bigger than the denominator so it it
4 3/8
8 * 63 = 8 * ? + 8 * 3 = ?
Okay, so we have 8 * 63, and it is broken down to 8 * ? + 8 * 3.
63 - 3 = 60, so our number should be 60.
8 * 63 = 8 * 60 + 8 * 3 = ?
To find the last number, we can just multiply 8 * 63, which is 504.
8 * 63 = 8 * 60 + 8 * 3 = 504